2006
DOI: 10.1002/jnr.20742
|View full text |Cite
|
Sign up to set email alerts
|

Brain dysmyelination and recovery assessment by noninvasive in vivo diffusion tensor magnetic resonance imaging

Abstract: Diffusion tensor magnetic resonance imaging (DT-MRI) was applied for in vivo quantification of myelin loss and regeneration. A transgenic mouse line (Oligo-TTK) expressing a truncated form of the herpes simplex virus 1 thymidine kinase gene (hsv1-tk) in oligodendrocytes was studied along with two induced phenotypes of myelin pathology. Myelin loss and axonal abnormalities differentially affect values of DT-MRI parameters in the brain of transgenic mice. Changes in the anisotropy of the white matter were assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
223
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(250 citation statements)
references
References 50 publications
(55 reference statements)
24
223
3
Order By: Relevance
“…Slight decreases of the axial diffusivity ( p ϭ 0.059) in both splenium and genu of the corpus callosum at w12 might express axonal damage that is often observed in MS demyelinated lesions and believed to be one of the reasons for recovery failure (Trapp et al, 1999). We previously demonstrated in a transgenic mouse model (Harsan et al 2006) that the axonal morphology influences the axial diffusion values. Cuprizone-treated mice show also axonal modifications that could be related to the observed small modifications in the axial diffusivity.…”
Section: Assessment Of Cuprizone Effects In Brainmentioning
confidence: 94%
See 1 more Smart Citation
“…Slight decreases of the axial diffusivity ( p ϭ 0.059) in both splenium and genu of the corpus callosum at w12 might express axonal damage that is often observed in MS demyelinated lesions and believed to be one of the reasons for recovery failure (Trapp et al, 1999). We previously demonstrated in a transgenic mouse model (Harsan et al 2006) that the axonal morphology influences the axial diffusion values. Cuprizone-treated mice show also axonal modifications that could be related to the observed small modifications in the axial diffusivity.…”
Section: Assessment Of Cuprizone Effects In Brainmentioning
confidence: 94%
“…Consequently, cuprizone demyelinated mice serve as excellent models for the development of in vivo noninvasive imaging methods, capable of diagnosis and following the course of demyelinating disease over time (Yu et al, 2004;Merkler et al, 2005;Sun et al, 2006). DT-MRI is one of the most powerful and sensitive techniques that proved its sensitivity in the case of myelin disorders in human (Ciccarelli et al, 2001;Agosta et al, 2005) and animal models (Song et al, 2005;Harsan et al, 2006Harsan et al, , 2007Deboy et al, 2007). The method has particular importance because it offers special insight in white matter pathology, providing specific information about the condition of myelin or axons.…”
Section: Assessment Of Cuprizone Effects In Brainmentioning
confidence: 99%
“…White matter physiology, particularly myelination, has been proposed to contribute to Individual differences in cognitive processing speed (e.g., Luciano et al 2004) based on the wellestablished role of myelin thickness and axon diameter in determining conduction velocity (Waxman 1980). Recent reports of relations between DTI measures of fractional anistropy (FA) -an indirect measure of myelination (Harsan et al 2006) and other WM microstructural properties (Beaulieu 2002) -and cognitive reaction time support the proposal of a white matter contribution to variability in processing speed (Bucur et al 2007;Gold et al 2007;Madden et al 2004;Manoach et al 2007;Nestor et al 2007;Tuch et al 2005;Westerhausen et al 2006). On this basis, we reasoned that WM microstructure might also contribute to the timing of evoked neural responses, which are a more direct measure of the timing of neural responses than behavior.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the mainstay of diffusion imaging studies of the rodent brain have used high-field animal scanners (4.7-11.7T) (Guilfoyle, et al, 2003;Harsan, et al, 2006;Hoehn-Berlage, et al, 1999;Nair, et al, 2005;Tyszka, et al, 2006;Verma, et al, 2005;Zhang, et al, 2002). Additionally, because adequate signal-to-noise ratio (SNR) requires prolonged scan times, many of these experiments have been conducted on in vitro brain tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, because adequate signal-to-noise ratio (SNR) requires prolonged scan times, many of these experiments have been conducted on in vitro brain tissue. Only a few studies report in vivo results (mice: (Guilfoyle, et al, 2003;Harsan, et al, 2006;Nair, et al, 2005); rats: (Boretius, et al, 2004;Hoehn-Berlage, et al, 1999;Lee, et al, 2006;Lin, et al, 2005;Numano, et al, ;). Most reports have displayed color orientation maps rather than fiber tracking, with exceptions being Xue et al , who demonstrated fiber reconstruction at 4.7T with 0.22 × 0.31 × 0.50-mm 3 resolution in 2 h, and Lee et al (Lee, et al, 2006), who reported quantitative fiber tracking at 1.5T in which 0.63 × 0.63 × 0.50-mm 3 resolution required 110 min of scanning.…”
Section: Introductionmentioning
confidence: 99%